Psychological and Pedagogical Factors of Activating the Masters Students Cognitive Interests to the Study of Foreign Languages - Oliinyk, Maria; Zhurat, Yuliya; Davydiuk, N (My University, 2019)
Motivation is a major factor in activity, including cognitive one. Pedagogical and psychological factors stimulate cognitive interest, cognitive and educational activity. Activating the cognitive interests of students to study foreign languages becomes successful due to the correspondence of the content of educational material organization, ways and methods of teaching, the provision of personal meaning educational material, the establishment of subject-subject relations in the educational process, the use of psychological and pedagogical methods of stimulation by the teacher of students’ cognitive interest and cognitive activity. The future professionals (students) successful training of foreign language, professionally oriented communication is impossible without defining a single concept that is the training clear strategy and tactics.Formation of foreign-language professional-oriented competence is possible through that modeling in the educational process typical situations of real professional communication that arise in different spheres of life and relate to different topics.The communicative activity of students during the training of professionally oriented communication in a foreign language is a system consisting of organizational and motivational, informational and procedural and criterion-effective components that derive from the social nature of human activity and create the best conditions for the improvement of the entire system of student communicative activities in relation to formation of foreign professional competence.
педагогіки та психології дошкільної освіти
Keywords: cognitive interest; motivation; cognitive interest activation; personal meaning of educational activity; block organization of training